Photocatalytic treatment of petroleum refinery wastewater by ZnO nanoparticles immobilized on a concrete substrate - Hameed, Kassim Kadhim; Mohammed, Wadood T.; Mohammed, Sohaib J. (Iraqi Journal of Chemical and Petroleum Engineering, 2025)
The petroleum industry's operations often involve substantial water usage, resulting in vast quantities of contaminated water, with a volume of the polluted water body estimated as about half the quantity of oil utilized in the refinement process. This wastewater contains various substances that are harmful to the health and environment, including hydrocarbons, heavy metals, and other toxic chemicals. This research aims to explore photocatalytic synthesis of zinc oxide nanoparticles to treat oil refinery wastewater. The effectiveness of this approach will be assessed by measuring the rate of Chemical Oxygen Demand (COD) reduction while identifying the best conditions to achieve the best performance and maximizing energy efficiency. Various operational conditions that drive the influence on the wastewater treatment process were investigated, including pH of 3, 5, 7, and 9, flow rate of 0.25, 0.5, 0.75, and 1.0 l/min, and the amount of the photocatalyst used per unit area (20, 40, 60, 80, 100 g/m2). Under optimum conditions, the photocatalytic method was applied with the following parameters: a COD of 1278 mg/l, a pH level of 7, a catalyst density of 80 g/m2, an effluent flow of 0.25 l/min, an irradiation power of 65 W, and an airflow of 100 cubic centimeters per minute. After 120 minutes, the COD reduction efficiency reached 76%, requiring energy consumption of 173.4 kW.hr/m3.